2009
DOI: 10.2466/pms.108.1.139-148
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Expert and Novice Soccer Players When Using Movement Precues to Shoot a Penalty Kick

Abstract: In the present study, effects of using precues of the goalkeeper's movements during a penalty kick on the penalty taker's response time and rate of success when selecting the points at which shots were taken were evaluated. 20 male players included 10 expert players (M=25.7 yr., SD=4.2 yr.) and 10 novices (M=22.1 yr., SD=2.5 yr.), whose response time, decision making, and foveal vision in a simulated penalty kick task were evaluated. Analysis showed greater decrease in response time for the expert group (102 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Previous research has revealed the ability of the goalkeepers to use advance cues in the penalty kick (e.g., Williams & Burwitz, 1993;McMorris & Colenso, 1996;Williams, 2000;Núñez, et al, 2005;Savelsbergh, et al, 2005;Panchuk & Vickers, 2006;Núñez, et al, 2009). During the treatment sessions, the Independent strategy group obtained a mean of successful goals per session almost twice that of the Dependent strategy group; thus, the use of cues permitted the goalkeepers to block those kickers who did not improve their results in the posttreatment sessions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous research has revealed the ability of the goalkeepers to use advance cues in the penalty kick (e.g., Williams & Burwitz, 1993;McMorris & Colenso, 1996;Williams, 2000;Núñez, et al, 2005;Savelsbergh, et al, 2005;Panchuk & Vickers, 2006;Núñez, et al, 2009). During the treatment sessions, the Independent strategy group obtained a mean of successful goals per session almost twice that of the Dependent strategy group; thus, the use of cues permitted the goalkeepers to block those kickers who did not improve their results in the posttreatment sessions.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, interest in the penalty situation in soccer has increased. Research has moved on from the classical study of utilization of anticipation cues, which distinguishes an expert from an inexperienced goalkeeper (e.g., Williams, 2000;Savelsbergh, Williams, Van der Kamp, & Ward, 2002;Núñez, Oña, Bilbao, & Raya, 2005;Savelsberg, Van der Kamp, Williams, & Ward, 2005;Núñez, Oña, Raya, & Bilbao, 2009), to studying the time limitations the penalty kicker is subject to as a function of the available visual information (Morya, Ranvaud, & Pinheiro, 2003;Castillo, Oña, Raya, & Martínez, 2005;Bakker, Oudejans, Binsch, & Van der Kamp, 2006;Van der Kamp, 2006).…”
mentioning
confidence: 99%
“…Interest in the penalty kick and the role of the goalkeeper in saving penalties has become a feature of recent sport science investigations. Some have focused on applying perceptual strategies to enhancing the performance of both the kicker and goalkeeper during the penalty kick (Hanvey, 1999;Poulter, Jackson, Wann, & Berry, 2005;Núñez, Oña, Raya, & Bilbao, 2009). Others have identified the strategies employed by successful goalkeepers by comparing expert and novice goalkeepers (Savelsbergh, Williams, van der Kamp, & Ward, 2002;Castillo, Oña, Raya, Bilbao, & Serra, 2010) and studying their body position before the kick is taken or observing the probability of success on the basis of the location of the kicked ball in the goal (Panchuk & Vickers, 2006;Bar-Eli, Azar, Ritov, Keidar-Levin, & Schein, 2007;Masters, van der Kamp, & Jackson, 2007;Bar-Eli & Azar, 2009;Núñez, Oña, Raya, & Bilbao, 2010).…”
mentioning
confidence: 99%
“…Based on studies focusing on the application of perceptual strategies, Núñez, et al (2009Núñez, et al ( , 2010 evaluated the anticipation of novice and expert players if goalkeepers' pre-cues were available. The results showed an explicit knowledge of pre-cues improved anticipation in both groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation